IMPLEMENTASI MODEL PEMBELAJARAN INKUIRI BERBANTUAN HANDOUT BERGAMBAR UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA SMP NEGERI 1 AMANDRAYA - Giawa, Ester Finister (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
This research aims to determine the increase in learning interest of class IX students through the application of the inquiry learning model assisted by pictorial handouts. The type of research is quantitative, descriptive in nature. The research population was class IX students of SMP Negeri 1 Amandraya, while the research sample was class IX students. This research data was analyzed using normality tests and hypothesis testing using the SPSS (Statistical Product and Service Solution) application version 22. The results of this research before using the inquiry learning model assisted by illustrated handouts were an average score of 35.6 for the final test in the cycle I, while after using the inquiry learning model assisted by pictorial handouts in the final test of cycle II, the average score was 78.6 in the good category. Suggestions from researchers for teachers are that it is best to use an inquiry learning model assisted by illustrated handouts in learning activities because it makes students understand more because it can increase students' interest in learning. Future researchers should carry out this research with a wider scope.